Comparison of catabolic rates of 13C‐labeled palmitic acid bound to the alpha and beta positions of triacylglycerol using CO2 expired from mice. Issue 5 (3rd December 2014) - Beppu, Fumiaki; Konno, Kaoru; Kawamatsu, Takashi; Nagai, Toshiharu; Yoshinaga, Kazuaki; Mizobe, Hoyo; Kojima, Koichi; Watanabe, Hiroyuki; Gotoh, Naohiro
Abstract We investigated the catabolic rate of 13C‐labeled palmitic acid (*P) bound to α (sn‐1) or β (sn‐2) position of triacylglycerol (TAG) using isotope‐ratio mass spectrometry. Specifically, we measured the 13C‐to‐12C ratio in CO2 expired from mice. After 30–75 min, *P bound to the α position was catabolized faster than that bound to the β position. Thereafter, the catabolic rate of *P bound to the β position increased and surpassed that bound to the α position. This indicated that binding position affected the catabolic rate of *P, possibly due to the different specificities of pancreatic lipase, lipoprotein lipase, and hepatic lipase. Next, we measured the catabolic rate of *P bound to TAG in combination with one of three unsaturated fatty acids (oleic acid, linoleic acid, or α‐linolenic acid). When *P was bound to the β position and Ln was bound to the α position, the catabolism of TAG was significantly higher than for other TAGs. This result suggests that fatty acid structure might affect the catabolism of counterpart fatty acids in TAG. Practical applications: Binding position to TAG affects fatty acid catabolism. The fatty acid desired to change to energy such as saturated fatty acid should be bound to the β position of TAG. In contrast, fatty acid desired to accumulate in our body such as polyunsaturated fatty acid should be bound at the α position of TAG because catabolism does not continue for a long time even though the fatty acid is catabolized quickly at first period. Our results can be applied to the design of structured lipid used for enteral nutrients, enteric nutrient, sports nutrients, etc. <inline-graphic xlink:href="ark:/27927/pgjkz1nn3r" content-type="ejlt201400326-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Comparisons of Δ13C from 13C‐labeled CO2 expired from mice that were administered emulsified triacylglycerol bound to 13C‐labeled palmitic acid (*P) at the α or β position of triacylglycerol. Fatty‐acid binding position affects the catabolic rate of fatty acids. (A): 1, 3‐dioleoyl‐2‐[1‐13C]‐palmitoyl glycerol (β‐O*PO) vs. 1, 2(2, 3)‐dioleoyl‐3(1)‐[1‐13C]‐palmitoyl glycerol (β‐OO*P), (B): 1, 3‐dilinoleoyl‐2‐[1‐13C]‐palmitoyl glycerol (β‐L*PL) vs. 1, 2(2, 3)‐dilinoleoyl‐3(1)‐[1‐13C]‐palmitoyl glycerol (β‐LL*P), (C): 1, 3‐diα‐linolenoyl‐2‐[1‐13C]‐palmitoyl glycerol (β‐Ln*PLn) vs. 1, 2(2, 3)‐diα‐linolenoyl‐3(1)‐[1‐13C]‐palmitoyl glycerol (β‐LnLn*P).